Repeatability of surface EMG during gait in children - Granata, Kevin P.; Padua, Darin A.; Abel, Mark F. (Gait & posture, 2005)
Although mean amplitude and ON–OFF timing of muscle recruitment and electromyography (EMG) activation during gait is achieved by an age of six to eight years in normally developing children, recruitment dynamics illustrated by the shape of the EMG waveform may require continued developmental practice to achieve a stable pattern. Previous analyses have quantified the repeatability of the EMG waveform in adult subjects, but EMG variability for a pediatric population may be significantly different. The goal of this study was to quantify intra-session and inter-session variability in the phasic EMG waveform patterns from the lower limb muscles during self-selected speeds of walking in healthy-normal children for comparison with adult variability in gait EMG. The variance ratio quantifies the repeatability of the integrated EMG waveform shape in a group of normally-developing children. Results reveal that between-session EMG waveform variability were similar in adult and pediatric populations, but within-session variability for the children was approximately twice the published value for adults. Clinical implications of this pediatric EMG variability suggest cautious interpretation of data from limited trial samples or inter-session changes in performance of gait data.